Urban PM₁₀ Monitoring in Malaysia: A Statistical Framework for Process Stability and Capability Assessment - Alias , Nurliana; Talib, Muzalwana Abdul (Journal of Quality Measurement and Analysis, 2026)
This study introduces a novel statistical framework for urban air quality assessment by applying the time-weighted Exponentially Weighted Moving Average (EWMA) control charts and process capability indices (CPI), to simultaneously diagnoses two aspects of the air quality: (1) stability (predictable air pollution behavior); and (2) capability (consistent compliance with national standards) in Four Process States framework to evaluate PM₁₀ concentrations in Petaling Jaya, Shah Alam, and Putrajaya from 2015 to 2019 using monthly observations. The dual-analysis approach of this study thereby offers a more comprehensive and diagnostically informative classification of system performance beyond conventional compliance monitoring. The results show that 13 of 15 city-year observations fall under the Threshold Process State, indicating all three urban areas experienced constant non-compliance throughout the study period. Shah Alam went through episodes of Chaos throughout 2015 and 2016. This was due to exposure to persistent elevated PM₁₀ levels, which might have posed significant health risks to the public during those years. Putrajaya potentially be a candidate for full compliance. The proposed framework serves as a diagnostic tool in distinguishing between structural pollution issues and temporary fluctuations, hence enabling more targeted and proactive interventions. Rather than relying solely on compliance status, policymakers can assess whether air quality systems are fundamentally capable of meeting regulatory standards. This offers more effective environmental regulation for better long-term urban planning and earlier risk detection. Additionally, it contributes to broader sustainability goals, particularly those related to public health and resilient urban governance.